The impact of brand image on consumer purchase intention : a study of the smartphone industry in Malaysia - Hasan, Rokibul (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2017)
The purpose of this study is to find out the effects among brand image, brand loyalty, perceived quality purchase intention towards smartphone. It also aims to explore the mediating role of perceived quality and brand loyalty on brand image and purchase intention. Applying the theory of brand image and brand loyalty, a structural equation model was developed and tested on 204 respondents from the Klang Valley, using a self-developed questionnaire. The findings suggest that perceived quality does not mediate the relationship between brand image and purchase intention towards smartphone. Brand image and brand loyalty have significant impact on purchase intention while brand loyalty partially mediates the relationship between brand image and purchase intention. The findings also suggest that the impact of perceived quality on purchase intention is not significant. The study suggests that the smartphone brands to build higher brand image to increase the brand loyalty among the consumers. As a result, brand image and brand loyalty will increase the purchase intention towards smartphone.